Organization of a macrocycle for the training of highly qualified female athletes specializing in modern pentathlon - Sevdalev, S. V.; Borovaya, V. A.; Netsvetaeva, E. S.; Vrublevskiy, E. P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and substantiate the structure of building a macrocycle for the training of highly qualified female athletes specializing in modern pentathlon.